Analysis of the Book "Arab Economics" at the Faculty of Islamic Economics and Business on Ibn Khaldun's Theory - Yasmar, Renti; Azizah, Fitriyana; Kurniawan, Rahadian (Tanwir Arabiyyah: Arabic as Foreign Language Journal, 2024)
The teaching of Arabic in Islamic universities faces many problems, including the lack of special educational materials and used by each teacher differently, the existing class is few than he had to perform for four skills, the lack of vocabulary to practice the language skill, and in addition to the lack of enthusiasm in learning Arabic only from the Faculty of Arabic Language Teaching only. The aim of this study is to know the objectives, material, method and evaluation of the book "Arab Economic" on the theory of Ibn Khaldun, and this research of the type of qualitative descriptive study, the researcher observed the Arabic book of economics, and the evidence and its sources of objectives, material, method and evaluation in the Arab book of economics, collected books and documents in the style of analysis of the doctrine of Mehlis and Hubermin. It is concluded that Ibn Khaldun's theory towards the goals, material, method and evaluation in this book Arabic economics is: the goal aspect includes improving thinking, improving society and improving spirituality suitable for improving thinking for the community of the Faculty of Economics with good Arabic language and the Holy Quran. In terms of the subject, it includes conversation, vocabulary, grammar and exercises to understand the language like the queen at the Faculty of Economics. In terms of method, it is appropriate to gradually or repetition, discussion and exemplary in the process of teaching economic Arabic writers. In terms of the calendar, it has exercises, exercises and songs to support the acquisition of the four language skills. The final result of this research is that the Arabic book of economics has helped students at the Faculty of Economics and Business to learn the fun Arabic language and train the four skills according to the practice of objectives, material, method and evaluation according to Ibn Khaldun.